MATHEMATICAL MODELING OF THE DETERMINATION OF LOCAL RESISTANCE IN THE WATER SUPPLY SYSTEM AND PRESSURE LOSS IN PIPES BY TRANSITION AREAS - M. A. Musajonov (Journals Park Publishing, 2023)
In this article, calculation work was carried out through a novel mathematical model of calculation using the formulas Nikuradze, Stokes, Blazius, Altshunya, Ciphrinsonva, Darcy-Veysbach and related developments in practical application of the local resistance generated in the water supply system in flowing streams in water pipes. In this case, it is possible to determine the Reynolds number, hydraulic resistance coefficient and pressure loss, calculated according to the fluid flow in the pipe.
Keywords: Local resistance, sharp expansion, sharp narrowing, flat narrowing, hydraulic resistance, equivalent roughness, Reynolds number, piezometric slope, laminar motion, turbulent motion, critical velocity.